IMPACT OF DIAGNOSTIC AND INTERVENTIONAL ENDOSCOPIC ULTRASONOGRAPHY IN CHILDREN - GARCIA,Larissa Latrilha (2022)
ABSTRACT Background: Endoscopic ultrasonography is used in the diagnosis and treatment of digestive diseases in adults. In children, its use is limited due to a lack of available expertise. Objective: This study aimed to evaluate the clinical impact of endoscopic ultrasonography on diagnostic and therapeutic strategy changes in pediatric patients. Methods: Over ten years, this study retrospectively and consecutively analyzed children aged ≤18 years who underwent endoscopic ultrasonography because of inconclusive imaging or laboratory tests. The indications, results, occurrence of adverse events, and clinical impact of the procedures were analyzed. The clinical impact was classified as major (when the findings led to changes in diagnosis and management), minor (change in diagnosis but not in management), or none (no change in diagnosis or management). Results: Overall, 107 children [77 (72%) of whom were female; mean age: 11.7 ± 4 years] underwent upper [102 (95.3%)] and lower [5 (4.7%)] endoscopic ultrasonography; 64 (58%) patients underwent diagnostic endoscopic ultrasonography, and 43 (42%) underwent interventional endoscopic ultrasonography. Endoscopic ultrasonography was used to investigate pancreaticobiliary, gastric, rectal, esophageal, duodenal, and mediastinal diseases in 81 (76%), 14 (13%), 5 (4.6%), 3 (2.8%), 2 (1.8%), and 2 (1.8%) patients, respectively. The clinical impact was significant in 81% of the children. Major and no clinical impact on pancreaticobiliary, gastrointestinal diseases, and mediastinal masses occurred in 50 (62%) and 13 (16%), 13 (54%) and 9 (37%), and 2 (100%) and 0 (0%) of the patients, respectively. Conclusion: This study evaluated the impact of diagnostic and interventional endoscopic ultrasonography in pediatric patients. When clinically and appropriately indicated, these procedures are safe and effective diagnostic or therapeutic interventions in pediatric patients with gastrointestinal or pancreaticobiliary disorders.